3D hierarchical porous graphene nanosheets as an efficient grease additive to reduce wear and friction under heavy-load conditions. (April 2020) - Ouyang, Tiancheng; Shen, Yudong; Yang, Rui; Liang, Lizhe; Liang, Hao; Lin, Bo; Tian, Zhi Qun; Shen, Pei Kang
Abstract: Improving tribological properties of grease is highly demanded for reducing energy consumption and mechanical equipment failure caused by friction under heavy-load conditions. Herein, 3D hierarchical porous graphene (3D HPGS), as a lithium grease additive, is investigated by the measurements of morphologies and wear volume loss of worn surface in three motion modes. The results demonstrate that the addition of graphene can significantly enhance the friction-reduction and anti-wear capacities of the grease and thus results in a much smoother worn surface. In particular, the grease with 0.3 wt% graphene can be reduced by 52.0% and 20.3% for the wear volume loss and friction coefficient respectively, compared to that of the original one. The outstanding anti-wear and friction-reduction properties of 3D HPGS is originated from the evidences that graphene can coat onto the rubbing interface and form protective films to prevent the direct contact of friction pairs, thus reducing the friction and wear. The results indicate the great potential for 3D HPGS as lubricant additives to save energy and prolong the mechanical equipment service life. Graphical abstract: Image 1 Highlights: 3D hierarchical porous graphene nanosheets (3D HPGS) is investigated as lithium grease additives. Three motion modes and four concentrations of 3D HPGS are applied under heavy-load conditions. Friction coefficient, wear and morphologies confirm the improvement of tribological properties. EDS and Raman spectrum reveal the lubrication mechanism of 3D HPGS.